SUCCESSFUL COLLABORATION BETWEEN DISCIPLINES IN A VIRTUAL TEACHING CONTEXT THROUGH THE APPLICATION OF DESIGN THINKING - Ivanova, Maya; Botev, Samuil; Angelova, Desislava; Vodenova, Pavlina (Innovation in Woodworking Industry and Engineering design, 2026)
The curriculum in the "Engineering Design (Interior and Furniture Design)" Bachelor program has frequently changed over the years regarding how and what kind of study modules are taught. In the 2020-2021 academic year, the teaching staff was presented with another novelty – the transition to full-time virtual training in practical design and purely artistic disciplines.In the context of introducing a new virtual education modality, the new teachers in the department decided to leverage the moment and test innovative ways of working that are widely applicable in their practices and were formerly introduced in their design training in foreign universities. Their approach was based on integrating design thinking with the traditional approach used in the program to bridge two separate study modules from the curriculum – "Graphic Design" and "Furniture Design for Public Spaces". In the process, the assistant professors introduced a few new tools, principles, and perspectives, all with the idea of raising the level of engagement and practical fieldwork experience among students, taking advantage of the positive aspects of working in a virtual environment.